2011
DOI: 10.1002/ir.388
|View full text |Cite
|
Sign up to set email alerts
|

Using college students' self‐reported learning outcomes in scholarly research

Abstract: Construct validity provides a framework for evaluating the adequacy and appropriateness of using students' self‐reports of learning outcomes in scholarly research. Evidence from a recent study concerning the relationships between academic environments and self‐reported learning outcomes, based on Holland's person‐environment fit theory, provides evidence of the appropriateness of using these self‐report data in scholarly research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…According to Pike (2011), self-report data is appropriate for scholarly research in which the goal is to identify relationships among measures that are grounded in a theoretical framework-such as the relationships between those learning outcomes that are believed to be promoted through collaborative learning, selected student engagement constructs, and instructional practices. Further support for the validity of self-reports of educational outcomes as indicators of learning is provided by Anaya (1999).…”
Section: Limitationsmentioning
confidence: 99%
“…According to Pike (2011), self-report data is appropriate for scholarly research in which the goal is to identify relationships among measures that are grounded in a theoretical framework-such as the relationships between those learning outcomes that are believed to be promoted through collaborative learning, selected student engagement constructs, and instructional practices. Further support for the validity of self-reports of educational outcomes as indicators of learning is provided by Anaya (1999).…”
Section: Limitationsmentioning
confidence: 99%
“…This study relied on students' self-reported practices. Although this may have impacted the data and survey results, nevertheless, there is considerable research that underscores the reliability of students' self-reported responses to questionnaires and surveys (Douglass, Thomson, & Zhao, 2012;Pike, 2011). The potential impact of socially desirable reporting was mitigated through the use of anonymous questionnaires.…”
Section: Limitationsmentioning
confidence: 99%
“…The research reported in this study compares the assessment practices of trained and calibrated observers to a third alternative: student self-report methods (for more on using student self-report data for assessment purposes, see Centra, 1993;Ebert-May et al, 2011;Pace, 1985;Pike, 2011). The notion of using student self-report data as a potential replacement for observation methods was questioned by many involved with our redesign program.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Astin (1971Astin ( , 1977, Kuh (2001), and Pace (1984Pace ( , 1985 on large samples of undergraduate students have resulted in highly useful and reliable data. In addition, Pike (2011) noted that "60 percent of the articles published in [higher education] journals in 2006 made use of self-report data from surveys" (p. 41). Pike also indicates that a second informal study on the same journals for 2010 yielded roughly 50% of data stemming from self-perceptions of students, alumni, faculty, and staff.…”
Section: Introductionmentioning
confidence: 99%